Photodynamic therapy using a new formulation of 5-aminolevulinic acid for wrinkles in Asian skin: A randomized controlled split face study. (June 2015) - Shin, Hyun Tae; Kim, Jun Hwan; Shim, Joonho; Lee, Jong Hee; Lee, Dong Youn; Lee, Joo Heung; Yang, Jun Mo
Abstract Background: Photodynamic therapy (PDT) with intense pulsed light (IPL) was proven effective for photorejuvenation. Recently, a new formulation of 0.5% 5-aminolevulinic acid (ALA) liposomal spray has been available. We designed a randomized split face study to evaluate usefulness and safety of IPL-PDT using a liposomal spray for periorbital wrinkles in Asians. Methods: Patients received three treatments every 3 weeks. The half of the face was treated with IPL-PDT and the other half with long pulsed Nd:YAG laser (LPNY). Skin fluorescence was measured using a spectrophotometer for the guidance of PDT treatment. Wrinkle score was marked by two-blinded independent dermatologists. Results: One patient dropped out due to 3-d lasting erythema on PDT side. The difference of mean reduction in lower and lateral periorbital wrinkle score on PDT side between the first and the last visit was statistically significant (p = 0.008 and p = 0.001, respectively). Lateral periorbital wrinkles treated with PDT showed better results than LPNY-treated sides. Twenty-five percent of patients reported good to excellent outcomes. Conclusion: This study demonstrated that PDT with a liposomal spray provided modest wrinkle reduction without serious adverse effect and it might be a promising treatment modality for wrinkle treatment in Asians.